Current concepts and future strategies in the management of intracranial germinoma. Issue 1 (2014) - Kortmann, Rolf-Dieter
Abstract : Radiation therapy is the backbone in the management of intracranial germinoma. In localized disease chemotherapy followed by whole brain irradiation is the present standard providing cure rates in excess of 90%. Craniospinal irradiation alone in metastatic disease provides equally excellent outcome. Chemotherapy is able to convert macroscopic to microscopic disease permitting a dose reduction to the tumor site and possibly the ventricular system and is investigated in prospective trials. Chemotherapy alone cannot replace radiotherapy as sole treatment. Whole-ventricular radiotherapy followed by a boost to tumor site without chemotherapy might be feasible. New treatment technologies such as intensity-modulated radiotherapy or proton therapy permit a dose reduction to non-target brain. Data on functional outcome are conflicting and based on small heterogeneous series only mandating prospective investigations.